Two sides of the same coin: adaptation of BCIs to internal states with user-centered design and electrophysiological features. Issue 2 (3rd April 2022) - Han, Yiyuan; Ziebell, Philipp; Riccio, Angela; Halder, Sebastian
ABSTRACT: The ideal brain–computer interface (BCI) adapts to the user's state to enable optimal BCI performance. Two methods of BCI adaptation are commonly applied: User-centered design (UCD) responds to individual user needs and requirements. Passive BCIs can adapt via online analysis of electrophysiological signals. Despite similar goals, these methods are rarely discussed in combination. Hence, we organized a workshop for the 8th International BCI Meeting 2021 to discuss the combined application of both methods. Here we expand upon the workshop by discussing UCD in more detail regarding its utility for end-users as well as non-end-user-based early-stage BCI development. Furthermore, we explore electrophysiology-based online user state adaptation concerning consciousness and pain detection. The integration of the numerous BCI user state adaptation methods into a unified process remains challenging. Yet, further systematic accumulation of specific knowledge about assessment and integration of internal user states bears great potential for BCI optimization.